Keterampilan Kolaborasi dan Literasi Digital dalam Meningkatkan Literasi Numerasi Mahasiswa - Vera Mandailina; Hartika Aulia; Abdillah Abdillah; Syaharuddin Syaharuddin (Lembaga Bale Literasi, 2025)
Research on improving numeracy literacy among students is important to do considering that numeracy competence is one of the main indicators in facing the challenges of the digital era and the increasingly complex needs of the labor market. This research aims to examine the role of collaboration skills and digital literacy in improving students' numeracy literacy. This type of research is qualitative with a Systematic Literature Review (SLR) approach. Literature sources were obtained from indexed databases, namely Dimensions and Scopus, with a coverage of publications within the last ten years. The results of the analysis show that collaborative skills, digital literacy integration, and the implementation of educational policies have a significant contribution to strengthening student numeracy literacy. Various collaborative and digital learning models such as Cooperative Integrated Reading and Composition (CIRC), Participatory Action Research (PAR), and technology-based interactive platforms are considered effective in increasing student engagement and understanding numeracy concepts in depth. The findings are expected to be the basis for developing adaptive and relevant learning strategies in the context of higher education in the digital era.